Illegality, Inc. : clandestine migration and the business of bordering Europe - Andersson, Ruben, 1977- (California series in public anthropology, 2014)
"In this groundbreaking ethnography, Ruben Andersson, a gifted anthropologist and journalist, travels along the clandestine migration trail from Senegal and Mali to the Spanish North African enclaves of Ceuta and Melilla. Through the voices of his informants, Andersson explores, viscerally and emphatically, how Europe's increasingly powerful border regime meets and interacts with its target - the clandestine migrant. This vivid, rich work examines the subterranean migration flow from Africa to Europe, and shifts the focus from the "illegal immigrants" themselves to the vast industry built around their movements. This fascinating and accessible book is a must-read for anyone interested in the politics of international migration and the changing texture of global culture."--Provided by the publisher